(untitled) (Al-Academy, 2016)
The subject of this study is one of the most interactive media networks, which is the Instagram.The study uses a descriptive approach and focuses on how Instagram turns from a media tool to a marketing tool. The study problematic consists of this question: How Instagram turns to a marketing tool, and what are the advantages and the disadvantages for that?This study highlights the definition of Instagram, the creation of it and its improvement, the Instagram in Bahrain, the Instagram uses, the Instagram as a marketing tool, and the advantages and disadvantages of using Instagram for marketing.The study confirms that Instagram is a new media network, and focuses on how it develops on later stages and mentions the increase of the percentages of its users which make it a real competitor to several new media networks such as Facebook and Twitter. The study also shows the presence of multiple uses for Instagram, including the media sector, networking sector, as well as commercial sector.The study concluded that Instagram became one of the most prominent and important tool in the interactive media network specially as marketing tool. Many companies, institutions and individuals used Instagram as part of the marketing strategies. The study also showed that the commercial use of the Instagram has many negative effects, mainly in reliance on display striking images and attractiveness to attract consumers, which may cheat, and fraud people. Finally, the study recommended enacting legislation to follow up on Instagram accounts for marketing in a legal framework, and censor these accounts